Magnetic Hybrid Carbon via Graphitization of Polystyrene–co‐Divinylbenzene: Morphology, Structure and Adsorption Properties. Issue 10 (15th July 2016) - Cesano, Federico; Rahman, Mastabur M.; Bardelli, Fabrizio; Damin, Alessandro; Scarano, Domenica
Abstract: Multilayer graphitic nanosheets/nanoshells have been obtained via pyrolysis at 850 °C of poly(4‐ethylstyrene‐co‐divinylbenzene) (PS‐co‐DVB) by inflowing Fe(II)‐acetylacetonate (Fe(ACAC)2 ) into the pores of the polymer. Iron‐free PS‐co‐DVB was also pyrolyzed at the same temperature, thus highlighting the effective role of the catalyst in promoting the graphitization at relatively moderate temperatures. It will be shown that under longer annealing times at 850 °C in presence of Fe3 C and α‐Fe the carbon precursor undergoes an extensive graphitization as compared to the iron‐free material. Catalyst nanoparticles were found to be encapsulated into graphitic nanoshells providing effective barriers to the oxidation processes, thus preserving the magnetic properties. On the other hands, the metallic nanoparticles can be oxidized under environmental conditions, with negative effects on the magnetic properties, which points out the need to preserve the material for applications. The hybrid multilayer graphitic carbon, tested in magnetically driven adsorption experiments of methylene blue dye, can find application in the water purification processes. Abstract : Multilayer graphitic nanosheets/nanoshells incorporating magnetic nanoparticles have been prepared by catalytic graphitization at low temperature (850 °C). The peculiar hybrid character together with the mesopore properties make the material suitable for an effective dye removal from water solutions.